2012
DOI: 10.1111/j.1865-1682.2012.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Chickens Caused by Avian Influenza Virus A/H5N1 Delivered by Aerosol and Other Routes

Abstract: Summary This study presents results of the study of infectivity of avian influenza virus (AIV) A subtype H5N1 strains isolated from agricultural birds across the territory of the Russian Federation and CIS countries. The results of the susceptibility of chickens to the AIV isolates delivered by the aerosol route and the dissemination of the virus in the organs of infected birds are presented. As was observed, the sensitivity of birds to AIV by the aerosol route of infection is 30 times higher than by intranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…Furthermore, the frequency of infection and the titers of virus detected were significantly higher in specimens from chickens inoculated with aerosols than with intranasal drops. These findings combined with our previous report (6) are in agreement with those of Sergeev et al (19), who demonstrated that an HP A/Chicken/Kurgan/05/2005 (H5N1) virus administered to chickens in aerosols spread more rapidly along the respiratory tract than the virus inoculated by intranasal drops. Likewise, clinical signs appeared earlier in ferrets infected through inhalation of aerosolized A/Vietnam/1203/2004 (H5N1) virus compared to those infected by intranasal drops (11).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the frequency of infection and the titers of virus detected were significantly higher in specimens from chickens inoculated with aerosols than with intranasal drops. These findings combined with our previous report (6) are in agreement with those of Sergeev et al (19), who demonstrated that an HP A/Chicken/Kurgan/05/2005 (H5N1) virus administered to chickens in aerosols spread more rapidly along the respiratory tract than the virus inoculated by intranasal drops. Likewise, clinical signs appeared earlier in ferrets infected through inhalation of aerosolized A/Vietnam/1203/2004 (H5N1) virus compared to those infected by intranasal drops (11).…”
Section: Discussionsupporting
confidence: 93%
“…A human clinical study of influenza infection reported that the 50% infectious dose (ID 50 ) by aerosol inhalation was approximately 100-fold less than by inoculation with intranasal drops (24). In accord with that report, studies in chickens have shown that the ID 50 values of both HPAI H5N1 and LPAI H9N2 viruses were substantially lower by aerosol inoculation than by intranasal drops (6,19). Sergeev et al (19) found that aerosolized HPAI H5N1 virus was rapidly spread to various organs via the respiratory infection in chickens.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…The importance of the oro-faecal transmission in spread of AIV is well recognized (Sergeev et al, 2013). However, in the dynamics of HPAI infection, other factors such as the host, virus strain, immunity and environment, which all contribute to the outcomes of H5N1 infections, are not well understood (Spickler et al, 2008;Kwon & Swayne, 2010;Hénaux & Samuel, 2011;Pantin-Jackwood et al, 2013;Wibawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The AAHLnucleoprotein ELISA is a competitive ELISA that had been proved to be sensitive and specific for detection of antibody to the NP of type-A influenza viruses in birds and mammals (Sergeant et al 2009;Sergeev et al 2013) and was used in the surveillance of AI in wild and domesticated birds in Australia (OCVO 2010).…”
Section: Discussionmentioning
confidence: 99%